Mekanisme Penetapan Ambang Batas (Threshold) Terhadap Stabilitas Sistem Presidensial Dan Sistem Multipartai Sederhana Di Indonesia - Abadi, Songga Aurora; Arsil, Fitra (UI Scholars Hub, 2022)
This journal discusses the Threshold Mechanism for the Stability of the Presidential System and the Simple Multiparty System in Indonesia, with the aim of knowing concretely the essential conditions for the realization of an effective presidential government, through the substance of the policy setting limits in force in Indonesia, and the implications of setting thresholds on the stability of Indonesia's presidential and multiparty systems. This research was conducted using normative legal research methods, through library research, with prescriptive research typologies that are conducting intensive, in-depth and detailed and comprehensive approaches to explore deeply about research issues. The results showed that during the general election in the reform era, various rules around thresholds were imposed in order to realize simple multiparty and presidential stability, the rules were in the form of the requirements for the establishment of political parties, the requirements for political parties to participate in general elections, the threshold for votes to be able to participate in general elections next (electoral threshold), the threshold of the vote acquisition of political parties to sit in parliament (parliamentary threshold), the threshold for fraction formation (fractional threshold), the threshold for presidential nomination (presidential threshold). The policy to determine the threshold has legal consequences: 1) Political parties are not recognized as legal entities; 2) Political parties cannot participate in the election; 3) Political Parties cannot obtain seats in the DPR. Although the requirements for party establishment, party registration as a legal entity, and party requirements for participating in elections have effectively reduced the number of political parties, the electoral threshold has failed in practice because the number of parties fused is relatively low and the parliamentary threshold policy is getting worse every year high, but the number of political parties in parliament is still in extreme multiparty conditions.